PENERAPAN STRATEGI ACTIVE LEARNING TIPE SMALL GROUP WORK DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD INPRES BONTO-BONTOA KECAMATAN SAMBA OPU KABUPATEN GOWA - Hamzah Pagarra; Nurhaedah; Henny Kiki Palindrung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low science learning outcomes of fifth-grade students at SD Inpres Bonto-Bontoa. This study aims to describe the implementation of the active learning strategy of small group work in improving the science learning outcomes of fifth-grade students at SD Inpres Bonto-Bontoa, Somba Opu District, Gowa Regency. The method used is a qualitative approach and classroom action research (CAR). The implementation of the research action was carried out in 2 cycles, and each cycle consisted of 2 meetings. The research was conducted at SD Inpres Bonto-Bontoa, Somba Opu District, with research subjects consisting of one teacher and 22 students, including 10 male students and 12 female students. Data collection techniques included observation, tests, and documentation. Meanwhile, data analysis was conducted descriptively and qualitatively. The research results indicate that the teacher's activity during the learning process in cycle I was in the sufficient category and showed improvement in cycle II to be in the very good category. Student learning activities also showed improvement, from the sufficient category in cycle I to the very good category in cycle II. Student learning test results improved from the sufficient category in cycle I to the good category in cycle II. The conclusion of this study shows that the implementation of the Small Group Work type of Active Learning strategy can improve the science learning outcomes of fifth-grade students at SD Inpres Bonto-Bontoa, Somba Opu District, Gowa Regency.